Analysis of Factors Influencing the Socio-Emotional Development of Elementary School Children at the Advent Education Foundation in Palopo City, 2025 - Amiruddin, Asri; Fadli , Fadli; Eka Sari, Erni; Hastuty, Dewi (AACENDIKIA: Journal of Nursing, 2025)
Socio-emotional development is a critical aspect of growth during school-age years. It is characterized by the child’s ability to adapt to their environment, establish friendships, and manage emotions, thoughts, and behaviors. Developing these skills early is essential to ensure children grow and develop as expected. This study aimed to identify the factors influencing socio-emotional development among elementary school children at the Advent Education Foundation in Palopo City in 2025. A quantitative analytic descriptive design with a cross-sectional approach was used. The study employed total sampling, involving 32 respondents from grades V and VI. The instruments included the Strength and Difficulties Questionnaire (SDQ) to assess socio-emotional problems and a separate questionnaire to evaluate influencing factors. Data were analyzed using SPSS with the Chi-Square test. Statistical analysis revealed no significant relationship between socio-emotional development and internal factors such as child health, home atmosphere, or family economic status. However, external factors showed significant associations: family dynamics (p = 0.022), learning environment (p = 0.003), and peer interaction (p = 0.041). These findings indicate that socio-emotional development in children is significantly influenced by external factors, particularly family support, the comfort of the learning environment, and peer relationships. Therefore, strengthening family involvement and fostering positive learning and peer environments are vital for enhancing children's socio-emotional development.